Experiences and perspectives on pregnancy and motherhood in elite athletes – a qualitative study - Marlene Zahl Marken; Emilie Frederikke Mass Dalhaug; Lone Friis Thing; Frank Eirik Abrahamsen; Kari Bø; Lene Annette Hagen Haakstad (Sexual and Reproductive Health Matters)
Elite athletes routinely undertake strenuous training routines, which often involve high-intensity sessions. However, there are knowledge gaps in how they experience training during pregnancy and subsequent return to sport. Combined with inadequate financial and contractual safety, female athletes may jeopardise their careers when starting families. This study aimed to describe female athletes’ experiences and perspectives related to pregnancy and motherhood within the context of elite sports in Norway. We interviewed five world-class athletes between October 2022 and April 2023, using a descriptive qualitative approach. Full interview transcripts were analysed based on a reflexive thematic analysis model. Five overarching themes were identified: (1) uncertainty, (2) lack of supportive networks, (3) physical capacity, (4) the impact of postpartum return to sports on maternal health, and (5) combining motherhood and elite sports. Our findings emphasise the challenges that Norwegian pregnant and postpartum athletes face in balancing motherhood with successful careers, highlighting the importance of providing adequate support systems to ensure their health and the well-being of their child.